Diffracting our stories: New questions about roles in and beyond South African university writing centres - Moore, Jean; Dison, Laura (Critical Studies in Teaching and Learning, 2025)
South African writing centre scholarship reveals how writing centres have responded to changing circumstances in higher education. Much of this scholarship reflects processes of ongoing reflection and reflexivity, engaging and interrogating notions of resilience, agency and literacy in different ways. In this paper, we identify three broad writing centre narratives apparent in this scholarship. We then trouble some of these stories, including our own, by turning to bystander theory as a lens and diffraction as a methodology. This allows us to question how writing centre narratives assign the roles of victim, perpetrator and upstander in higher education, and in writing centres specifically. We wonder together about the roles assigned in these stories and their effects. We call for a more critical approach to understanding South African writing centre work and argue that our stories and roles, by over-focussing on the micro-level and neglecting the meso- and macro-levels, may unintentionally shield universities from having to enact systemic transformation.